2006
DOI: 10.1152/advan.00063.2006
|View full text |Cite
|
Sign up to set email alerts
|

Study of physiological responses to acute carbon monoxide exposure with a human patient simulator

Abstract: Human patient simulators are widely used to train health professionals and students in a clinical setting, but they also can be used to enhance physiology education in a laboratory setting. Our course incorporates the human patient simulator for experiential learning in which undergraduate university juniors and seniors are instructed to design, conduct, and present (orally and in written form) their project testing physiological adaptation to an extreme environment. This article is a student report on the phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Virtual lab simulations are being increasingly used to enhance the development of professional skills in various fields, such as healthcare [ 1 ] and education, including courses in chemistry [ 2 , 3 ], biotechnology [ 4 ], and medical genetics [ 5 ]. Virtual learning simulations have also been applied to organs [ 6 , 7 ] virtual dissections [ 8 ], and in human patient simulators [ 9 ]. Advantages of virtual laboratory simulations include cost-effectiveness, increased engagement of students with learning materials, and elimination of biosafety concerns [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Virtual lab simulations are being increasingly used to enhance the development of professional skills in various fields, such as healthcare [ 1 ] and education, including courses in chemistry [ 2 , 3 ], biotechnology [ 4 ], and medical genetics [ 5 ]. Virtual learning simulations have also been applied to organs [ 6 , 7 ] virtual dissections [ 8 ], and in human patient simulators [ 9 ]. Advantages of virtual laboratory simulations include cost-effectiveness, increased engagement of students with learning materials, and elimination of biosafety concerns [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… 16 It has also been used as an experimental tool to simulate bodily responses to extreme environments such as carbon monoxide poisoning during occupational mining accidents. 17 High-fidelity simulators were designed to test medical devices and interventions, especially in emergency situations, 18 , 19 before their translation into clinical research or clinical practice, allowing safer clinical human studies and clinical practice. It can be concluded that the METI HPS accurately reproduces real clinical situations.…”
Section: Introductionmentioning
confidence: 99%
“…There was confusion and insecurity about how to review another student's work. Unfortunately, the practice of peer review was not a priority for students relative to other, substantive assignments within these courses (3,14). Consequently, after 2 yr, we removed the peer review element and relied on detailed instructor feedback exclusively.…”
mentioning
confidence: 99%